Diagnostic Biomarker Hsa_circ_0126218 and Functioning Prediction in Peripheral Blood Monocular Cells of Female Patients With Major Depressive Disorder - Bu, Tianyi; Qiao, Zhengxue; Wang, Wenbo; Yang, Xiuxian; Zhou, Jiawei; Chen, Lu; Yang, Jiarun; Xu, Jia; Ji, Yanping; Wang, Yini; Zhang, Wenxin; Yang, Yanjie; et al. (Frontiers in Cell and Developmental Biology, 2021)
Introduction: Although major depressive disorder has brought huge burden and challenges to society globally, effective and accurate diagnoses and treatments remain inadequate. The pathogenesis that for women are more likely to suffer from depression than men needs to be excavated as well. The function of circRNAs in pathological process of various diseases have been widely investigated. This study aims to explore potential diagnostic biomarker circRNA of female patients with major depressive disorder and to investigate its role in pathogenesis. Methods: First, an expression profile of circRNAs in the peripheral blood monocular cells of MDD patients and healthy peripherals were established based on high-throughput sequencing analysis. In addition, top ten differentially expressed circRNAs were quantified by quantitative real-time PCR to explore diagnostic biomarkers. To further investigate the function of biomarker in pathogenesis of MDD, bioinformatics analysis on downstream target genes of biomarker was carried out. Results: There is a mass of dysregulated circRNAs in PBMCs between female MDD patients and healthy controls. Among the top ten differentially expressed, circRNAs Hsa_circ_0126218 is more feasible to be diagnostic biomarker. The expression level of Hsa_circ_0126218 displayed upregulation in patients with MDD and the area under the operating characteristic curve of has_circ_0126218 is 0.801 (95% CI 0.7226-0.8791, p<0.0001). To explain the competing endogenous RNA role of has_circ_0126218 in pathogenesis of female MDD, a has_circ_0126218-miRNA-mRNA network was established. Gene Ontology Resource and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis stated that some of enriched pathways of downstream of Hsa_circ_0126218 are close relevant to MDD. Moreover, established a protein-protein network for further screen out the hub genes (PIK3CA, PTEN, MAPK1, CDC42, Lyn, YES1, EPHB2, SMAD2, STAT1 and ILK). The function of Hsa_circ_0126218 was refined by constructing a verified circRNA-predicted miRNA-Hub gene subnetwork. Conclusion: Hsa_circ_0126218 has been considered as new female MDD biomarker and the pathogenesis of female MDD by hsa_circ_0126218 regulating its downstream has been predicted. The findings may lay a function for further improve the way to early detect depression, diagnose effectively, monitor complications conveniently, treat precisely and prevent recurrence timely.